2019
DOI: 10.1016/j.eucr.2019.100871
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented ureteral stent extraction by antegrade and retrograde access:using ureteroscope and nephroscope

Abstract: there are different complications of using ureteral stents in urology field, one of the challenging complications is stent fragmentation which is frequent in patients with missed and forgotten stents accompanying encrustation, presented case was 70- year-old female, left single kidney with stent fragmentation After TUL and stent insertion one year ago, because of retained fragments in kidney, ureter, and bladder, combined antegrade and retrograde approach was used for stent fragments extraction, for preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Thereby reduceing the risk of postoperative infection. Different from other reports [10][11][12], this case is treated in one position combined with intravesical lithotripsy, retrograde ureteroscopy and percutaneous nephrolithotripsy. The whole process of puncture and removal of stent tube is monitored.…”
Section: Discussionmentioning
confidence: 85%
“…Thereby reduceing the risk of postoperative infection. Different from other reports [10][11][12], this case is treated in one position combined with intravesical lithotripsy, retrograde ureteroscopy and percutaneous nephrolithotripsy. The whole process of puncture and removal of stent tube is monitored.…”
Section: Discussionmentioning
confidence: 85%
“…The exact reason for this early SSF is difficult to ascertain from the current report but it is unlikely to be due to stent encrustation and calcification like the previous reports. [4][5][6]9 One possible cause is the presence of a very hostile urine environment in these two patients. The first patient was a construction laborer who works outside in a very hot environment and had long periods of dehydration.…”
Section: Discussionmentioning
confidence: 97%
“…Aging of the stent has also been recognized as an important cause for stent fragmentation 10,14 . In this regard, reviewing the literature indicated that SSF had occurred in stents which have been neglected or forgotten for long periods ranging between one year to as long as 15 years which led to stent encrustations and crystal formation 4‐6,9 . There was only one report of SSF which occurred after two months of insertion 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations